The Effect of Olfactory Marketing on The Sensory Perception of The Customer : Analytical Research of The Opinions of Managers in a Number of First-Class Hotels in The City of Erbil - محمد مجيد, هيوا (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The research seeks to find out the extent of the impact of scent marketing on the sensory perception of customers from the point of view of managers in first-class hotels in the city of Erbil, and to achieve the objectives of the research was designed questionnaire was distributed to managers in (11) hotels, which numbered (76) managers. To measure the relationship and impact between the two variables, the statistical methods of the social sciences (SPSS) were used in the analysis and testing of research hypotheses that stipulate the existence of a correlation and influence between the two variables, and one of the most prominent results of the research is the agreement of most respondents on the existence of a relationship and a positive effect between the olfactory marketing variable and the sensory perception variable.